(untitled) (Research, Society and Development, 2025)
The identification of acidic and basic substances is a fundamental concept that has gained prominence as a didactic alternative for teaching Chemistry and Biology. This study proposes the use of aqueous extracts from the flowers of White Hibiscus (Hibiscus rosa-sinensis L.), Glory Tree (Tibouchina granulosa (Desr.) Cogn.), Blue Trumpet Vine (Thunbergia grandiflora Roxb.), and leaves such as Red Leaf Lettuce (Lactuca sativa L.) and Bloodleaf (Iresine herbstii) as natural pH indicators, providing an accessible and sustainable experimental approach while facilitating and enhancing Chemistry and Biology education for high school students. The experimental proposal of this study aligns with the National Curricular Parameters (PCN+), by encouraging content contextualization and interdisciplinary interaction, as well as promoting the use of experimental classes to advance scientific knowledge. The main results indicate that the aqueous extracts used performed excellently as acid-base indicators, making them a strongly recommended and viable alternative for teaching Chemistry and Biology. Furthermore, the proposed experimental activity enhances students’ understanding of pH concepts and the properties of acids and bases, while also fostering critical thinking and scientific inquiry. This proposal is innovative as it employs, for the first time in educational literature in Brazil, aqueous extracts from the flowers of Blue Trumpet Vine (Thunbergia grandiflora Roxb.) and the leaves of Red Leaf Lettuce (Lactuca sativa L.) and Bloodleaf (Iresine herbstii) as natural pH indicators. This approach aims to contribute to science education by aligning with socioconstructivist principles, providing a hands-on learning experience based on experimentation.